A qualitative analysis of unintended effects of a digital conditional cash transfer intervention to encourage healthcare utilization in Southern Madagascar - Franke, Mara Anna; Neumann, Anne; Nordmann, Kim; Suleymanova, Daniela; Ravololohanitra, Onja Gabrielle; Knauss, Samuel; Emmrich, Julius (BMC health services research, 2025)
Cash transfer interventions, including those using mobile money, are becoming increasingly widespread, particularly in Sub-Saharan Africa. As such interventions can have significant positive and negative unintended consequences, further analyses are needed to identify these consequences.
Gesehen am 28.08.2025